2016
DOI: 10.1016/j.jmii.2014.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Fluoroquinolone-resistant and extended-spectrum β-lactamase-producing Escherichia coli from the milk of cows with clinical mastitis in Southern Taiwan

Abstract: Lacking virulence genes examined, genetic diverse E. coli isolates are unrelated to human pathogenic E. coli. Enhancing sanitation in milk processing and transportation is needed to eliminate multidrug-resistant (MDR), fluoroquinolone-resistant, and ESBL-producing E. coli isolates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 49 publications
4
39
0
4
Order By: Relevance
“…The RmtD variant has been found less frequently. Other than the report from Yang et al (123), another recent report has been published from Brazil, on one E. coli isolate from a diseased horse producing RmtD and harboring the bla CTX-M- 15 and aac(6′)-Ib-cr genes (125). The RmtE methylase was reported for the first time from commensal E. coli isolates from healthy calves in the United States (126).…”
Section: Resistance To Aminoglycosides By Target Modificationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The RmtD variant has been found less frequently. Other than the report from Yang et al (123), another recent report has been published from Brazil, on one E. coli isolate from a diseased horse producing RmtD and harboring the bla CTX-M- 15 and aac(6′)-Ib-cr genes (125). The RmtE methylase was reported for the first time from commensal E. coli isolates from healthy calves in the United States (126).…”
Section: Resistance To Aminoglycosides By Target Modificationsmentioning
confidence: 99%
“…To date, the global picture indicates that antimicrobial susceptibility of E. coli in mastitis remains high. In particular, extended-spectrum β-lactamases (ESBLs) or overexpressed cephalosporinases (AmpCs) produced by E. coli and conferring resistance to broad-spectrum cephalosporins have been sporadically isolated from milk samples (13)(14)(15)(16). Those families of antimicrobial agents may also be prescribed in newborns affected by diarrhea.…”
Section: E Coli In Animals: a Pathogenic And A Commensal Bacteriummentioning
confidence: 99%
“…The second continent with the highest number of countries reporting E-ESBL in cattle is Asia, which shows description of E-ESBL in 13 countries (China, Hong Kong, India, Indonesia, Iran, Israel, Japan, Lebanon, Malaysia, Saudi Arabia, South Korea, Thailand and Taiwan), highlighting China and India which are the fourth and fifth largest cattle producers in the world (Adler et al, 2015;Ali et al, 2017;Barzan et al, 2017;Diab et al, 2016;Hassan et al, 2015;Hinthong et al, 2017;Kamaruzzaman, 2015;Koovapra et al, 2016;Ohnishi et al, 2013a;Su et al, 2016;Sudarwanto et al, 2016;Tark et al, 2017). They have different roles in the import and export scenario, as India is the world's largest exporter of cattle and China the largest importer, since its internal production is not sufficient for internal consumption (USDA et al, 2017).…”
Section: Asiamentioning
confidence: 99%
“…Most genes encoding this type of antimicrobial resistance are located in conjugative plasmids or integron systems, and could be exchanged readily between enterobacteria species, facilitating their dissemination (CARATTOLI, 2013;WOODFORD et al, 2011). Current studies have reported the presence of ESBL producing E. coli in food, such as meat, milk and different types of cheese (GUNDOGAN;AVCI, 2013;SU et al, 2016;TEKINER;OZPINAR, 2016;VRABEC et al, 2015). Once beta-lactam resistant E. coli strains have become a global emerging problem in the last few years, carbapenems have been one of the main therapy options against human infections, including those caused by ESBL-producing bacteria (GENC et al, 2016;SPELLBERG et al, 2011).…”
Section: Introductionmentioning
confidence: 99%